MWCNT-Fe3O4 / silicon carbide fiber nano composite paper as well as preparation method and application thereof
By modifying MWCNT and Fe3O4 nanoparticles on silicon carbide fiber paper, MWCNT-Fe3O4/silicon carbide fiber nanocomposite paper is formed, which solves the problems of high density and poor corrosion resistance of existing electromagnetic shielding materials, and achieves lightweight, efficient and high-temperature electromagnetic shielding effect.
Patent Information
- Application Number
- CN202510233930.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-04-18
AI Technical Summary
The existing electromagnetic shielding materials have high density, poor corrosion resistance, and the shielding mechanism is mainly reflected, which is prone to secondary electromagnetic pollution, and the high-temperature resistance of carbon fiber paper is insufficient.
MWCNT-Fe3O4/silicon carbide fiber nanocomposite paper is used to modify multi-walled carbon nanotubes (MWCNT) and Fe3O4 nanoparticles on the surface of silicon carbide fiber paper to form a conductive network and magnetic loss medium, improving the electromagnetic shielding effect.
It realizes the electromagnetic shielding effect of lightweight, efficient, high temperature resistant and broadband, avoids the problems of high density and poor corrosion resistance of traditional materials, and reduces the electromagnetic reflectivity.
Smart Images

Figure CN119843510A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nanocomposite material preparation, and in particular to a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper and a preparation method and application thereof. Background Art
[0002] At present, the rapid development of the fifth generation of wireless communications and personal wearable electronic products has caused electronic radiation pollution, which not only hinders the normal operation of the equipment and shortens its service life, but also affects people's physical health. Therefore, taking necessary measures to eliminate the interference of electromagnetic waves is crucial to protecting people's life and health and the safety of electronic equipment. Researchers usually use electromagnetic shielding materials to reduce electromagnetic radiation. Traditional electromagnetic shielding materials are mostly metal materials with good electrical conductivity. While they have good electromagnetic shielding performance, they also have the disadvantages of high density and poor corrosion resistance. The shielding mechanism is mainly reflection, which is easy to produce secondary electromagnetic pollution. Therefore, the development of new materials with electromagnetic wave absorption as the main shielding method has gradually become a research hotspot. Among them, the porous structure of paper has interfacial polarization and multiple scattering effects on electromagnetic waves, which can effectively attenuate electromagnetic waves and reduce reflection. At the same time, the paper-based composite material prepared by papermaking wet forming technology has the advantages of low density, strong flexibility, and flexible design, and has broad development prospects in the field of electromagnetic shielding of wearable devices. Silicon carbide fiber is a ceramic fiber with high specific strength, high specific modulus, high temperature resistance, oxidation resistance, chemical corrosion resistance and excellent electromagnetic wave absorption characteristics. However, there are few research reports on the use of silicon carbide fibers to prepare silicon carbide fiber paper, which leads to relatively backward technology in related fields. Silicon carbide fiber paper-based materials have the characteristics of flexibility, high porosity and low density, and have special application advantages in the field of electromagnetic shielding.
[0003] According to the data, there is no patent report on silicon carbide fiber paper. In the invention patent CN114561831A, only the method of enhancing the performance of carbon fiber paper with silicon carbide particles is mentioned. The invention provides a carbon fiber paper with enhanced electromagnetic loss capacity by silicon carbide and a preparation method thereof, the method comprising the following steps: step 1, dispersing a mixture of carbon fiber and aramid fibrillation with a dispersant aqueous solution, the mass ratio of carbon fiber and aramid fibrillation is (50-90): (10-50), and then forming the obtained slurry into a carbon fiber paper wet paper web; step 2, first pressing the carbon fiber paper wet paper web, and then vacuum drying at a constant temperature to obtain a carbon fiber base paper; step 3, impregnating the carbon fiber base paper in a mixed ethanol solution of phenolic resin and silicon carbide, and then taking it out and drying it to obtain a carbon fiber paper with enhanced electromagnetic loss capacity by silicon carbide. Aramid fibrillation is introduced as an auxiliary forming fiber and silicon carbide is a dielectric loss medium to prepare a carbon fiber paper that is resistant to high temperature, has strong environmental adaptability, is light and thin, and has strong electromagnetic shielding ability. However, due to the use of only silicon carbide particles for reinforcement, the prepared carbon fiber paper still has insufficient high temperature resistance.
[0004] Due to the limitations of the preparation of carbon fiber paper, the reinforcing material used is silicon carbide particles, which theoretically have lower temperature resistance than silicon carbide fiber paper, mainly because of the difference in the main materials. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper.
[0006] The second object of the present invention is to provide a method for preparing MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper. The preparation method of the present invention is simple and controllable and suitable for industrial production.
[0007] The third object of the present invention is to provide an application of MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The invention discloses a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper. The MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper consists of silicon carbide fiber paper, and MWCNT and Fe3O4 nanoparticles modified on the surface of the silicon carbide fiber paper.
[0010] The MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper provided by the present invention uses silicon carbide fiber paper as a matrix, and simultaneously modifies MWCNT and Fe3O4 nanoparticles on the surface of the paper. The silicon carbide fiber has the characteristics of high temperature resistance, oxidation resistance, chemical corrosion resistance, light weight, and certain absorption performance. The MWCNT has the characteristics of high conductivity and low magnetic loss. The Fe3O4 nanoparticles have low conductivity and good magnetic loss performance. In the low frequency band, materials with high magnetic permeability have good electromagnetic shielding effect, and materials with high electrical conductivity in the high frequency band have good shielding effect. Specifically, due to its shape anisotropy and high aspect ratio, the MWCNT has a fast axial The charge transfer rate and the larger interface polarization area can form a conductive network to transform the incident electromagnetic waves and form a certain electromagnetic shielding effect, while the Fe3O4 nanoparticles can enhance the electromagnetic shielding effect of the low channel and improve the impedance matching of the material. In this way, in the low frequency band, due to the addition of Fe3O4 nanoparticles, there is also a good electromagnetic shielding effect. In the high frequency band, due to the addition of MWCNT, the electromagnetic wave conversion is further improved to form a shielding effect. With silicon carbide fiber as the main skeleton of the absorbing material, the three are matched to promote complementarity, so that the MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper provided by the present invention is a lightweight, efficient, high temperature resistant, broadband electromagnetic shielding material.
[0011] In the actual operation process, the inventors also tried other highly conductive carbon materials, and it turned out that only MWCNT and Fe3O4 nanoparticles could achieve the best performance through synergy. Even single-walled carbon nanotubes could not achieve the effect of the present invention due to dispersion problems.
[0012] The invention discloses a method for preparing MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper, comprising the steps of uniformly mixing MWCNT slurry and nano Fe3O4 precursor solution to obtain slurry, adding an aqueous polymer adhesive to the slurry to obtain MWCNT-Fe3O4 impregnation liquid, and immersing silicon carbide fiber paper in the MWCNT-Fe3O4 impregnation liquid. After immersion, the MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper is dried to obtain the MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper.
[0013] In a preferred solution, the mass fraction of MWCNT in the MWCNT slurry is 10-15%. In the present invention, the MWCNT slurry is an externally purchased aqueous dispersion of multi-walled carbon nanotubes.
[0014] According to a preferred embodiment, the nano Fe3O4 precursor solution is obtained by dissolving a trivalent iron salt in hot water to obtain a trivalent iron solution, then adding a divalent iron salt to the trivalent iron solution under stirring to dissolve the iron source solution, then adding an alkaline solution to adjust the pH value until the iron source solution completely turns black to obtain a nano magnetic liquid, and then washing the nano magnetic liquid until it is neutral.
[0015] Further preferably, in the iron source solution, Fe 3+ with Fe 2+ The molar ratio is 1.5-2:1.
[0016] Further preferably, the trivalent iron salt is selected from Fe(OH)3 and / or Fecl3.6H2O, and the divalent iron salt is selected from FeSO4.7H2O and / or FeCl2.4H2O.
[0017] Further preferably, the alkaline solution is selected from at least one of aqueous ammonia, sodium hydroxide solution or potassium hydroxide solution.
[0018] In a preferred embodiment, the mass ratio of the MWCNT slurry to the nano-Fe3O4 precursor solution is 10-50:40-90, preferably 20-30:40:50.
[0019] In the present invention, the addition amount of MWCNT slurry and nano-Fe3O4 precursor solution needs to be effectively controlled. If there are too many MWCNTs, electromagnetic waves will be reflected and affect the wave absorption performance. If there are too few MWCNTs, a good conductive path cannot be formed, and the electromagnetic shielding effect is reduced. Too much nano-Fe3O4 precursor solution leads to too few Fe3O4 nanoparticles and cannot provide sufficient magnetic loss medium. Too much leads to uneven material distribution and increases the weight of fiber paper, which does not meet the lightweight requirements and reduces the conductive effect of the material.
[0020] In a preferred embodiment, the water-based polymer adhesive is selected from at least one of water-based polyurethane, water-based epoxy resin, and water-based acrylic emulsion.
[0021] In a preferred embodiment, the mass fraction of the aqueous polymer adhesive in the MWCNT-Fe3O4 impregnation solution is 5%-40%, preferably 10-15%.
[0022] In the present invention, MWCNT and nano-Fe3O4 particles are modified on the surface of silicon carbide fiber paper by using an aqueous polymer adhesive. The amount of aqueous polymer adhesive added needs to be controlled. If too much aqueous polymer adhesive is added, the filler ratio will be reduced, thereby reducing the electromagnetic shielding effect. If too little aqueous polymer adhesive is added, there will be no forming material, resulting in a lower structural strength of the fiber paper.
[0023] In a preferred embodiment, the silicon carbide fiber paper is prepared by wet felting of short-cut silicon carbide fibers, and the length of the short-cut silicon carbide fibers is 2 to 15 mm. The inventors have found that by wet felting of short-cut silicon carbide fibers of the above length, silicon carbide fiber paper with high porosity, low density and excellent wave absorbing performance can be obtained.
[0024] Preferably, the density of the silicon carbide fiber paper is 15 g / ㎡-200 g / ㎡.
[0025] Further preferably, the preparation process of the silicon carbide fiber paper is: adding silicon carbide fiber to a nano-dispersion liquid to form a uniform suspension, and filtering out the dispersion liquid by suction filtration, wherein the nano-dispersion liquid is composed of the following components by weight: 0.5-25 parts of a surfactant, 0.2-15 parts of fumed silica, 0.1-10 parts of a thickener, 0.1-0.5 parts of a defoaming agent, 0.5-10 parts of a softener, and 39.5-98.6 parts of water.
[0026] Preferably, the soaking time is 1-10 minutes.
[0027] The present invention also provides an application of MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper, and the MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper is applied to the field of electromagnetic shielding.
[0028] Compared with the prior art, the MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper prepared by the present invention has the following beneficial technical effects:
[0029] ① The silicon carbide fiber paper used in the present invention is prepared by wet felting of short-cut silicon carbide fibers. Compared with traditional metal shielding materials and silicon carbide fiber paper prepared by other methods, it is lighter and has better wave absorbing performance.
[0030] ② Silicon carbide fiber is used as the main body to fully utilize the high temperature resistance, oxidation resistance, chemical corrosion resistance and excellent electromagnetic wave absorption characteristics of silicon carbide fiber.
[0031] ③It adopts water-based formula and has excellent environmental friendliness.
[0032] ④ Silicon carbide fiber paper is modified by multi-walled carbon nanotubes and Fe3O4 nanoparticles. MWCNT has the characteristics of high conductivity and low magnetic loss. Fe3O4 nanoparticles have low conductivity paramagnetism and good magnetic loss performance. Materials with high magnetic permeability in the low frequency band have good electromagnetic shielding effect, and materials with high electrical conductivity in the high frequency band have good shielding effect. Silicon carbide fiber is used as the main skeleton of the absorbing material. The combination of the three promotes complementarity and greatly reduces the electromagnetic reflectivity of the silicon carbide fiber paper, so that the MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper provided by the present invention is a lightweight, efficient, high temperature resistant, broadband electromagnetic shielding material. At the same time, it avoids the problems of uneven dispersion, poor composite performance with fiber, and significant increase in surface density when added to fiber paper, which affects the lightweight of the fiber paper, etc. when using traditional carbon black and ferrite powder, carbonyl iron powder and other fillers.
[0033] ⑤ The product preparation process is simple, has good repeatability and the ability to scale up production, fast preparation speed, high product uniformity, and good properties of being light and flexible. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is the MWCNT-Fe3O4 impregnation solution;
[0035] Figure 2 It is MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper;
[0036] Figure 3 This is the reflectivity test result of the unmodified original silicon carbide fiber paper in comparative example 1;
[0037] Figure 4 The reflectivity test results of MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper corresponding to Example 1;
[0038] Figure 5 The reflectivity test results of MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper corresponding to Example 2 are shown. DETAILED DESCRIPTION
[0039] The present invention will be further described below with reference to the embodiments.
[0040] Comparative Example 1
[0041] Step 1, prepare 5mm long silicon carbide fiber, add it to the nano-dispersion liquid, use a disperser to disperse it, wait for about 5 minutes to obtain a uniformly dispersed silicon carbide fiber dispersion, and filter the dispersion liquid by suction filtration to obtain silicon carbide fiber base paper (other parameters of the preparation process are the same as Example 1 of patent CN117945732A);
[0042] Step 2, soak the silicon carbide fiber paper prepared in step 1 in 15% aqueous polyurethane emulsion for 3 minutes, and dry it in a blast drying oven at 80°C to obtain unmodified silicon carbide fiber paper. The absorption and reflectivity results of the unmodified silicon carbide fiber paper are as follows: Figure 3 As shown, the lowest level is -7.28dB at 30.73GHZ.
[0043] Comparative Example 2
[0044] Step 1, prepare 5m long silicon carbide fiber, add it to the nano-dispersion liquid, use a disperser to disperse it, wait for about 5 minutes to obtain a uniformly dispersed silicon carbide fiber dispersion, and filter the dispersion liquid by suction to obtain the silicon carbide fiber base paper.
[0045] Step 2, using 15wt% aqueous polyurethane emulsion as the base material, adding 10g MWCNT slurry (MWCNT mass fraction is 10%), and preparing MWCNT nano impregnation solution for standby use:
[0046] Step 3, soak the silicon carbide fiber paper prepared in step 1 in the MWCNT nano impregnation solution prepared in step 2 for 3 minutes, and send it into a blast drying oven to dry at 80°C to obtain MWCNT / silicon carbide fiber nanocomposite paper. The prepared MWCNT / silicon carbide fiber nanocomposite paper has a uniform appearance, and the absorption reflectivity result reaches the lowest -19.48dB at 6.48GHZ.
[0047] Example 1
[0048] Step 1, prepare 5mm long silicon carbide fiber, add it to the nano-dispersion liquid, use a disperser to disperse it, wait for about 5 minutes to obtain a uniformly dispersed silicon carbide fiber dispersion, and filter the dispersion liquid by suction filtration to obtain silicon carbide fiber base paper (other parameters of the preparation process are the same as Example 1 of patent CN117945732A);
[0049] Step 2: Take a certain amount of water in a beaker, heat it to 30°C, turn on magnetic stirring, add 23g FeCl3.6H2O to the beaker and stir to dissolve, then add 8g FeCl2.4H2O and stir to dissolve. Add concentrated ammonia water dropwise to the above solution, adjust the pH to about 12, and obtain nano magnetic liquid after the solution turns completely black, and wash it with distilled water and ethanol until it is neutral for use.
[0050] Step 3, 30g MWCNT slurry (MWCNT mass fraction is 15%) and 40g nano magnetic liquid are mixed evenly, and 15wt% aqueous polyurethane emulsion is used as a base material to prepare MWCNT-Fe3O4 nano impregnation liquid for use;
[0051] Step 4, soak the silicon carbide fiber paper prepared in step 1 in the MWCNT-Fe3O4 nano impregnation solution prepared in step 3 for 3 minutes, and dry it in a blast drying oven at 80°C to obtain MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper. The prepared MWCNT@Fe3O4@silicon carbide fiber nanocomposite paper has a uniform appearance and a wave absorption reflectivity of Figure 4 As shown: The lowest value is -29.28dB at 6.92GHZ.
[0052] Example 2
[0053] Step 1, prepare 5mm long silicon carbide fiber, add it to the nano-dispersion liquid, use a disperser to disperse it, wait for about 5 minutes to obtain a uniformly dispersed silicon carbide fiber dispersion, and filter the dispersion liquid by suction filtration to obtain silicon carbide fiber base paper (other parameters of the preparation process are the same as Example 1 of patent CN117945732A);
[0054] Step 2: Take a certain amount of water in a beaker, heat it to 40°C, turn on magnetic stirring, add 6g Fecl3.6H2O to the beaker and stir to dissolve, then add 4g FeSO4.7H2O and stir to dissolve. Take NaOH solution and add it dropwise to the above solution, adjust the pH to about 12, and when the solution turns completely black, the nano magnetic liquid is obtained, and it is washed with distilled water and ethanol until it is neutral for use.
[0055] Step 3, 20g of MWCNT slurry (MWCNT mass fraction is 15%) and 50g of nano magnetic liquid are mixed evenly, and 10wt% aqueous polyurethane emulsion is used as a base material to prepare MWCNT-Fe3O4 nano impregnation liquid for use;
[0056] Step 4, soak the silicon carbide fiber paper prepared in step 1 in the MWCNT-Fe3O4 nano impregnation solution prepared in step 3 for 5 minutes, and send it into a blast drying oven to dry at 100°C to obtain MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper. The prepared MWCNT@Fe304@silicon carbide fiber nanocomposite paper has a uniform appearance, a sample thickness of 0.35mm, a surface density of 30g / ㎡, and a wave absorption reflectivity of Figure 5 As shown: 2-4GHZ is less than -1dB, with a minimum of 6.6dB; 5.6-10GHZ is less than -15dB, with a minimum of -31.39dB at 7.14GHZ; 10-15GHZ is less than -7dB, with a minimum of -15.5dB; 28-34GHz is less than -15dB, with a minimum of -27dB. It can be seen that the MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper provided by the present invention is lightweight and has excellent electromagnetic shielding effect in a wide frequency band.
Claims
1. A MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper, characterized in that: The MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper consists of silicon carbide fiber paper, and MWCNT and Fe3O4 nanoparticles modified on the surface of the silicon carbide fiber paper.
2. The method for preparing a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper according to claim 1, characterized in that: The MWCNT slurry and the nano-Fe3O4 precursor solution are uniformly mixed to obtain a slurry, an aqueous polymer adhesive is added to the slurry to obtain a MWCNT-Fe3O4 impregnation solution, the silicon carbide fiber paper is immersed in the MWCNT-Fe3O4 impregnation solution, and after the immersion is completed, the MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper is obtained by drying.
3. The method for preparing a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper according to claim 2, characterized in that: In the MWCNT slurry, the mass fraction of MWCNT is 10-15%.
4. The method for preparing a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper according to claim 2, characterized in that: The nano Fe3O4 precursor solution is obtained by dissolving a trivalent iron salt in hot water to obtain a trivalent iron solution, then adding a divalent iron salt to the trivalent iron solution under stirring to dissolve to obtain an iron source solution, then adding an alkaline solution to adjust the pH value until the iron source solution completely turns black to obtain a nano magnetic liquid, and then washing the nano magnetic liquid to neutrality.
5. The method for preparing a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper according to claim 4, characterized in that: In the iron source solution, Fe 3+ with Fe 2+ The molar ratio is 1.5-2:1; The ferric iron salt is selected from Fe(OH)3 and / or Fecl3.6H2O, and the ferrous iron salt is selected from FeSO4.7H2O and / or FeCl2.4H2O; The alkaline solution is selected from at least one of aqueous ammonia, sodium hydroxide solution or potassium hydroxide solution.
6. The method for preparing a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper according to claim 2, characterized in that: The mass ratio of the MWCNT slurry to the nano-Fe3O4 precursor solution is 10-50:40-90.
7. The method for preparing a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper according to claim 2, characterized in that: The water-based polymer adhesive is selected from at least one of water-based polyurethane, water-based epoxy resin, and water-based acrylic emulsion; In the MWCNT-Fe3O4 impregnation solution, the mass fraction of the aqueous polymer adhesive is 5%-40%.
8. The method for preparing a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper according to claim 2, characterized in that: The silicon carbide fiber paper is prepared by wet felting short-cut silicon carbide fibers, wherein the length of the short-cut silicon carbide fibers is 2 to 15 mm; The density of the silicon carbide fiber paper is 15g / ㎡-200g / ㎡; The preparation process of the silicon carbide fiber paper is as follows: adding silicon carbide fiber to a nano-dispersion liquid to form a uniform suspension, and filtering out the dispersion liquid by suction filtration. The nano-dispersion liquid is composed of the following components by weight: 0.5 to 25 parts of a surfactant, 0.2 to 15 parts of fumed silica, 0.1 to 10 parts of a thickener, 0.1 to 0.5 parts of a defoamer, 0.5 to 10 parts of a softener, and 39.5 to 98.6 parts of water.
9. The method for preparing a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper according to claim 2, characterized in that: The soaking time is 1-10 minutes.
10. The use of a MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper according to claim 1, characterized in that: The MWCNT-Fe3O4 / silicon carbide fiber nanocomposite paper is applied in the field of electromagnetic shielding.
Citation Information
Patent Citations
Carbon fiber paper with electromagnetic loss capability enhanced by silicon carbide and preparation method of carbon fiber paper
CN114561831A